Pericardial fluids or Cardiopulmonary Bypass—Is There a Major Culprit for Changes in Coagulation and Inflammation? - Gorki, Hagen; Nakamura, Julia; Kunert, Andreas; Hoenicka, Markus; Liebold, Andreas (The Thoracic and Cardiovascular Surgeon, 2020)
Background From the results of a previous study, it remained to be investigated if a perioperative rise of few tested coagulation and inflammation markers is caused by conventional cardiopulmonary bypass (CPB) itself or rather by direct recirculation of pericardial fluids.Methods Forty-eight patients operated on with conventional CPB for myocardial revascularization were randomized either for direct recirculation of pericardial suction fluids or for cell saving (CS).Results Thrombin–antithrombin complexes showed lower values intraoperatively in the CS group (p < 0.0001), and D-dimers tended to remain lower at intensive care unit arrival (p = 0.095). Tests of inflammation markers were less meaningful.Conclusion Direct recirculation of pericardial fluids rather than conventional CPB itself causes major intraoperative changes of some coagulation markers. Pericardial blood loss with direct recirculation should be kept to a minimum to avoid unnecessary activation of coagulation. Inflammation markers need further investigations.
Keywords: blood; coagulation; anticoagulation; cardiopulmonary bypass; CPB; coronary artery bypass grafting; surgery; CABG